Trammel net design engineering for operation with the sweeping method (Ciker net) - Zainal Wassahua; Sulaeman Martasuganda; Mulyono Sumitro Baskoro; Muhammad Fedi Alfiadi Sondita (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The active operation of a trammel net by a sweeping technique is commonly used by fishermen in Cilacap, which are often referred as ciker nets. They are operated by lowering the net in a straight line and pulling the tail end from a ship moving in a full circle, while the other end functions as a circular axis. The effect of active operation allows for changes in performance with time, such as easy lifting or less buoyancy, and the unstable display of gears. This makes it necessary to perform design engineering, especially on buoys, sinkers, and high nets. However, the suitable quantity of these components for ciker net has never been ascertained. Calculations about how many buoys, sinkers, and net height to add need to be done to enhance ciker net construction for active operation. This research aimed to determine the optimum configuration of buoys, sinkers, and net height, and determine the engineering design of ciker nets based on the optimum ratio of buoyancy force to the sinking force of the trammel net. Therefore, the parameters measured include hanging ratio, stretched net length, buoyancy force, and sinking force. The results showed that the optimum configuration of buoys, sinkers, and net height was 59 pieces, 341 pieces, and 1.5 m respectively. Changes in the design of ciker nets, especially in the three components that affect the addition of buoyancy and sinking force ratio were based on the comparison of the trammel nets which was 1:5 greater than the design owned by fishermen at 1:4.Keywords:Bouyancy forceSinking forceCiker netTrammel netShrimp